Involutional Entropion of The Upper Eyelid: A Rare Case Report: Poster Presentation - Case Report - Resident - Patrick Toar Panelewen; Yuliana Hartono (Majalah Oftalmologi Indonesia, 2023)
Introduction : Entropion is a condition in which the eyelid folds inward or the edge of the eyelid folds inward, causing the eyelashes, eyelid margin, and skin to touch the eyeball. The most common entropion is involutional which caused by the aging process, but reports of cases of involutional entropion in the upper eyelid are rare. Case Illustration : A 66-years-old woman presented with redness, foreign body sensation and teary on both eyes. No history of trauma or foreign body exposure. She had a history with similar complaint 2 years ago. Upper eyelid turn inward, dermatochalasis, and corneal abrasion of both eyes were found in ophtalmic examination. Patient was diagnosed with involutional entropion of the left upper eyelid and treated with anterior lamellar repositioning (ALR). A week after the ALR procedure, on examination it was found that the position of the left eye's upper eyelid was good, there was still minimal swelling, with intact sutures. Discussion : Involutional entropion generally occurs in elderly patients over 60 years old and is more common in women. Progressive senile changes in the structure of the eyelid cause the occurrence of involusional entropion. Involutional entropion in the upper eyelid is associated with dermatochalasis. One management option for involutional entropion is ALR, which aims to pull the folded-in eyelid margin outward. Conclusion : This case shows that involutional entropion on the upper eyelid can still occur, albeit very rarely. ALR can be a simple and safe surgical option for patients with involutional entropion on the upper eyelid.